Estudo experimental do efeito de escala em estruturas de concreto utilizando correlação de imagem digital - Ayrton Hugo de Andrade e Santos (2015)
The main objective of this work aims is analysis the inuence of the change of concrete composition in its structural response at dierent levels of scale, using as an experimental tool digital image correlation and acoustic emission. For this, it considered the inuence of the variables: coarse aggregates, ne aggregates, factor water/cement and strength. Experimental evidence of the phenomena associated with the size eect in con- crete structures and its heterogeneity are discussed from a historical thereof. From the appropriation of existing methodology, it has been applied to study the association of the phenomena described above. From elemental tests (axial compres- sion and diametrical compression modulus of elasticity) which analyzed parameters are the material properties and which parameters are structural properties. From three-points bending tests of beams of dierent sizes with a notch at the midspan were obtained load versus displacement curves that allowed a better understanding of the size eect and demonstrated the eciency of the digital image correlation technique for obtaining displacement measurements. With the results obtained it was possible to describe the fracture process zone - ZPF, introducing the concept of mean deformation as a measurement parameter of ZPF, and to measure the energy dissipated in the crack propagation process, it is possible to assert that process zone fracture is a property of the material, depending on the concrete composition.